2020
DOI: 10.35633/inmateh-62-30
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization on the Process of Adjustable Double Drum Castor Shelling Based on Discrete Element Method

Abstract: The shelling stress of the castor capsule is difficult to obtain by experiments, which is vital for the design of the key components for the shelling machine. The stress analysis of the shelling process of the castor capsule is carried out. In this study, the typical variety castor Tongbi 11 is taken as the research object, and the model of castor shelling is established. The stress and rate of shelling removal of the inner drum are analysed. The effects of size optimization on the shelling results were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The speed of the inner drum can be changed through the frequency converter, the position of the outer drum was adjusted to change the shell distance, and the amount of feed is adapted to fit the filling amount. The high speed camera was directed towards the observation window, and recorded the status of particles in the drum within 1.5 s to 8 s after feeding through high-speed photography (Hou et al, 2020). The experimental material was castor capsule Tongbi No.11, which was dried in Tongliao Academy of Agricultural Sciences, Inner Mongolia.…”
Section: Test Methods and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed of the inner drum can be changed through the frequency converter, the position of the outer drum was adjusted to change the shell distance, and the amount of feed is adapted to fit the filling amount. The high speed camera was directed towards the observation window, and recorded the status of particles in the drum within 1.5 s to 8 s after feeding through high-speed photography (Hou et al, 2020). The experimental material was castor capsule Tongbi No.11, which was dried in Tongliao Academy of Agricultural Sciences, Inner Mongolia.…”
Section: Test Methods and Instrumentsmentioning
confidence: 99%
“…The results suggested that the film was of tensile strength after its mechanical properties have been reinforced. The force and rate of shelling removal of the inner drum were analyzed (Hou et al, 2020). The results provided theoretical support for the design of the castor shelling machine.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, two-dimensional cameras have been widely used in the field of computer vision (Bewley et al, 2008;Chen et al, 2018;Junming et al, 2020). However, this technique has limitations in measuring animal body parameters, such as changes in light intensity, difficulty of background separation and image acquisition environment (Viazzi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%